Sustainable Accounting For SMEs in Indonesia: Implementation and Development Strategy - Fahmie, Arief; Pamungkas, Bambang; Munawar, Aang (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Sustainability accounting is becoming increasingly important for Small and Medium Enterprises (SMEs) in Indonesia in improving business sustainability and facing environmental challenges. This study aims to analyze the implementation of sustainable accounting in SMEs in Indonesia and develop effective development strategies. The results of the study indicate that SMEs in Indonesia have not yet fully implemented sustainable accounting, but have great potential to improve business sustainability. The proposed development strategies include increasing awareness and understanding of SMEs about sustainable accounting, developing appropriate accounting systems, and training and mentoring to improve SME capabilities. This study contributes to the development of sustainable accounting theory and practice in SMEs in Indonesia Keywords : sustainable accounting, small business, challenges, implementation